Left Ventricular Pseudoaneurysm after Left Ventricular Remodeling: Port Access Approach. Issue 1 (January 2014) - Sansone, Fabrizio; Ceresa, Fabrizio; Patanè, Francesco
Cases of left ventricular pseudoaneurysm caused by patch leakage after left ventricular remodeling are quite rare. We describe the case of a 66-year-old man operated on through a left thoracotomy using the Port Access platform to treat patch detachment after left ventricular remodeling.